Corporate Criminal Liability in Procurement of Goods and Services in Hospital - Meity Ardiana; Adriano Adriano; Kurniadi Doni; Yulianto Yulianto (Yuridika, 2023)
Procurement of goods and services for the benefit of the government is one of the tools to drive the wheels of economy in order to improve the national economy in order to create people's welfare and improve the quality of human resources. However, there are many problems in the implementation of the goods and services procurement program, such as mark-ups that exceeded the limit and law enforcement which was considered problematic, this resulted in the difficulty of determining which administrators were responsible for violations in the procurement of goods and services, given the complex form of management in a corporation that raises doubts about the possibility of the corporation to be held criminally liable and sentenced. Especially in hospitals which, at every level, every subject who carries out their duties and functions, can represent the hospital as a corporation. This article discusses corporate criminal responsibility for violations committed by Directors, Budget User Authorities, procurement committees and/or project executors in the procurement of goods and services in hospitals. This study will answer how is the criminal responsibility for violations committed by the Director and Committee in the procurement of goods and services at the Hospital and how is corporate criminal responsibility towards third parties for violations committed in the procurement of goods and services at the Hospital. The method used is qualitative and the approaches used are statute, conceptual, and case.